Reformasi Peradilan Pidana Ditinjau Dari Kasus Korupsi Jiwasraya “Studi Putusan Nomor 1052 K/PID.SUS/2022” - Assaqqaf, Syarifah Sukainah (Jurnal Jejak Hukum Indonesia (JHI), 2025)
This study examines the reform and optimization of law enforcement against corruption cases in Indonesia, focusing on the Jiwasraya case. Using a qualitative approach and document analysis, this research aims to identify the main challenges in law enforcement against corruption, analyze the factors influencing the success or failure of law enforcement in the Jiwasraya case, and formulate recommendations to enhance the effectiveness of law enforcement. The background of this issue stems from the major financial scandal at PT Asuransi Jiwasraya (Persero), which resulted in significant losses to the state. The research method used is normative legal research, involving the analysis of legal documents and relevant secondary data. The results of this study are expected to contribute to the reform of the legal enforcement system in Indonesia, strengthen the integrity of law enforcement agencies, and offer solutions to improve the criminal justice system in handling corruption cases in the future.